2012
DOI: 10.1021/ja309004c
|View full text |Cite
|
Sign up to set email alerts
|

Photodegradable Macromers and Hydrogels for Live Cell Encapsulation and Release

Abstract: Hydrogel scaffolds are commonly used as 3D carriers for cells because their properties can be tailored to match natural extra-cellular matrix. Hydrogels may be used in tissue engineering and regenerative medicine to deliver therapeutic cells to injured or diseased tissue through controlled degradation. Hydrolysis and enzymolysis are the two most common mechanisms employed for hydrogel degradation, but neither allows sequential or staged release of cells. In contrast, photodegradation allows external real-time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
73
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(74 citation statements)
references
References 26 publications
1
73
0
Order By: Relevance
“…At a certain thickness, depending on the light dose, the light is attenuated sufficiently such that the gel is no longer degrading. 35 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…At a certain thickness, depending on the light dose, the light is attenuated sufficiently such that the gel is no longer degrading. 35 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 …”
Section: Resultsmentioning
confidence: 99%
“…We found cell viability is somewhat compromised following encapsulation due to the polymerization conditions, most likely due to the APS/TEMED radical initiator since the macromers and polymerization conditions do not affect cell viability as discussed in the Supporting Information, S4). In another study, we found > 90% viability using a similar encapsulation protocol for human mesenchymal stem cells, 35 but it is difficult to compare viabilities from one study to another due to differences in composition, and to potential differences in sensitivity for different cell types. Mironi-Harpaz et al compared crosslinking efficiency versus cytotoxicity to bovine aortic smooth muscle cells.…”
Section: C2c12s Encapsulated In Folded Gelsmentioning
confidence: 96%
See 1 more Smart Citation
“…39 Light-Triggered Release of Iron Oxide Nanoparticles from Nanogels. Using the same chemistry, crosslinker 2 was also employed to synthesize light-degradable nanogels.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Initially, UV-Vis 11 light was used to trigger the release of drugs after inducing conformational changes 12,13 solubility variations 14 or the photodegradation of a specific group. 15,16 However, in-vitro studies demonstrated that the UV-Vis light can be toxic for living cells since it is widely absorbed by tissue, diminishing the light penetration to few microns. To solve these problems, NIR light has been used as external stimulus, which coupled with plasmonic systems provokes a local temperature increment that ends up with the drug release 17,18 .…”
mentioning
confidence: 99%